Autonomous mobile robots in sterile instrument logistics: an evaluation of the material handling system for a strategic fit framework. Issue 1 (2nd January 2023) - Fragapane, Giuseppe; Hvolby, Hans-Henrik; Sgarbossa, Fabio; Strandhagen, Jan Ola
Abstract: The logistics activities of sterile instruments are both labour- and cost-intensive. Automating sterile instrument transportation offers an excellent opportunity to reduce staff members' responsibilities and time committed to that task. With recent technological advances in material handling, autonomous mobile robots offer an innovative solution for transporting sterile instruments, especially in dynamic environments such as hospitals. However, hospital planners need guidance in deciding when to apply which material handling systems to achieve optimal performance. This study uses a multiple case study to map sterile instrument logistics and evaluate the transportation performance of material handling systems in terms of flexibility, productivity, quality/service, and costs. Applying contingency theory and analysing the relationships between material handling systems and hospital characteristics, we contribute with a strategic fit framework showing the ideal states to achieve high performance.